Tindak Tutur Ilokusi dalam Novel Perempuan di Titik Nol Karya Nawal El Saadawi - Nurul Karina Ningsih; Asep Purwo Yudi Utomo (Universitas Palan, 2026)
This research is part of the study of pragmatics, namely illocutionary speech acts. This research focuses on explaining illocutionary speech acts contained in the novel by Nawal El Saadawi entitled Perempuan di Titik Nol. The analysis of speech acts prioritizes language through its actual speakers. Illocutionary speech acts are defined as speech acts that contain intent and function or speech power. In an illocutionary speech act, the utterance gives rise to an action. Illocutionary speech acts are divided into five types, namely assertive, directive, expressive, declarative, and commissive illocutionary speech acts. The data obtained for this research are conversational utterances containing elements of illocutionary speech acts in the novel Perempuan di Titik Nol by Nawal El Saadawi. The research approach uses two methods, namely a pragmatic theoretical approach and a qualitative descriptive methodological approach. In collecting data, the researcher applied the listening method with advanced techniques of free listening and note-taking techniques. Meanwhile, for data analysis, the pragmatic equivalent method was used with formal and informal methods as a form of presentation of the data presented. The research results found 147 utterances containing illocutionary speech acts in this novel.